2016
DOI: 10.2337/dc16-0690
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy and Safety of Liraglutide Added to Capped Insulin Treatment in Subjects With Type 1 Diabetes: The ADJUNCT TWO Randomized Trial

Abstract: OBJECTIVETo investigate the efficacy and safety of liraglutide added to capped insulin doses in subjects with type 1 diabetes. RESEARCH DESIGN AND METHODSA 26-week, placebo-controlled, double-blind, parallel-group trial enrolling 835 subjects randomized 3:1 receiving once-daily subcutaneous liraglutide (1.8, 1.2, and 0.6 mg) or placebo added to an individually capped total daily dose of insulin. (-5.1, -4.0, and -2.5 kg for 1.8, 1.2, and 0.6 mg, respectively) versus placebo (-0.2 kg). Significant reductions i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

10
169
3
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 153 publications
(183 citation statements)
references
References 37 publications
10
169
3
1
Order By: Relevance
“…There was a higher rate of hyperglycaemic episodes with ketosis with liraglutide 1.8 mg compared with placebo, but there was no significant difference for the 1.2-and 0.6-mg groups compared with placebo (Table 3) [34]. Compared with the placebo group, the liraglutide 1.2 mg group had a higher rate of symptomatic and documented symptomatic hypoglycaemia but no significant difference in rate of severe or nocturnal hypoglycaemia.…”
Section: Glucagon-like Peptide-1 Receptor Agonistsmentioning
confidence: 90%
See 1 more Smart Citation
“…There was a higher rate of hyperglycaemic episodes with ketosis with liraglutide 1.8 mg compared with placebo, but there was no significant difference for the 1.2-and 0.6-mg groups compared with placebo (Table 3) [34]. Compared with the placebo group, the liraglutide 1.2 mg group had a higher rate of symptomatic and documented symptomatic hypoglycaemia but no significant difference in rate of severe or nocturnal hypoglycaemia.…”
Section: Glucagon-like Peptide-1 Receptor Agonistsmentioning
confidence: 90%
“…There were reductions in insulin doses in the liraglutide treatment groups, mainly through lower requirements of prandial insulin [34]. The HbA 1c reduction with liraglutide 1.8 mg was accompanied by improvements in 1, 5-anhydroglucitol, a postprandial hyperglycaemia surrogate, compared with placebo, and by reductions in post-breakfast, post-lunch, and bedtime glucose levels.…”
Section: Glucagon-like Peptide-1 Receptor Agonistsmentioning
confidence: 91%
“…15,19 This is intriguing and may be related to inappropriately high reduction in insulin doses. 15,19 This is intriguing and may be related to inappropriately high reduction in insulin doses.…”
Section: Discussionmentioning
confidence: 99%
“…However, CGM use and data interpretation requires training and experience, has had slow adoption, and its potential remains to be fully realized. Likewise, use of therapies currently approved for the treatment of type 2 diabetes have improved outcomes in T1D such as body weight and insulin dose reductions, insulin sensitization, lowering HbA1c, increasing time in desired glucose range and even reducing glycemic variability; however, most studies have shown responses span the gamut from nonresponders to super-responders [135][136][137][138][139] , thus emphasizing the need for strat-ified, precision medicine approaches. The novel class of SGLT inhibitors, both mono SGLT2 and dual SGLT1/2, are currently in pivotal T1D label expansion studies by manufacturers.…”
Section: Early Stage 3 T1dmentioning
confidence: 99%